O lugar da ponderação alexyana na doutrina brasileira: por uma reinterpretação à luz da crítica hermenêutica do direito - Neves, Isadora Ferreira (Universidade do Vale do Rio dos Sinos, 2014)
This dissertation aims to analyse how legal scholars in Brazil adopted Robert Alexy’s balancing theory of legal principles. In order to do so, it will work within a theoretical framework known as critical hermeneutics of law (“Crítica Hermenêutica do Direito” - CHD). This work is structurally divided in three parts. During the first, it will explain how Robert Alexy tailored the balancing theory of legal principle to be a critical response to the jurisprudence of values that was widespread in Germany and applied by its Supreme Court. The second chapter will analyse how Brazilian legal scholars adopted Alexy’s theory. In addition, it will explain the historical background surrounding its adoption, which will allow understanding how Brazilian peculiarities led to the assemblage of a very different balancing theory, far away from Alexy’s original works. This assemblage was essential to the development of two common concepts in Brazilian legal thinking: “neo constitutionalism” and “judicial activism”. The former was an attempt to overcome legal positivism, but failed due to the very nature of legal norms and the result of discretionary interpretations. The latter, as will be seen, is completely different of the judicialization of politics. This distinction allows understanding how judicial activism is inevitably away to institutionalise judges’ will of power. In the last chapter, the text will focus on how the theoretical framework proposed here (CHD) perceives Alexy’s balancing theory. In order to proceed with this, it will demonstrate three different but inherently linked approaches: first, the revolution of Martin Heidegger’s and Hans-Georg Gadamer’s idea of “method”; second, Ronald Dworkin’s thesis that law is an interpretive concept which needs integrity; third, Lenio Streck’s decision theory as an alternative to solve the problem of discretionary judicial decisions. Considering these relevant theoretical perspectives, this dissertation aims to propose a reflection upon usual assumptions that underlie the incorporation of Robert Alexy’s balancing theory by Brazilian legal scholars and show how it is incompatible with hermeneutical rationality.
Keywords: Teoria dos direitos fundamentais; Crítica hermenêutica do direito; Ponderação; Fundamental rights theory; Critical hermeneutics of law; Balancing theory; ACCNPQ::Ciências Sociais Aplicadas::Direito